Effect of Waste Marble Stone Fractions in Porous Asphalt Mixtures for Quality Improvement - Sa'dillah, M; Oktaviastuti, Blima; Malo, Yoskario Darman (Rekayasa, 2025)
Improving road transportation accessibility is essential for enhancing local social and economic activity in a country. One way to maintain the accessibility of the road network and ensure that users feel safe and comfortable is to maintain an adequate pavement surface layer throughout the duration of the network. Prolonged rain becomes one of the problems of paving the road surface. aims to achieve the following: (1) to determine the Marshall strength of the optimum asphalt content (OAC) value in the porous asphalt mixture; and (2) to determine the effect of the use of marble stone fraction waste on the characteristics of porous asphalt mixtures. Research method uses experimental research in the laboratory. Research will be conducted using the Australian Asphalt Pavement Association (AAPA) 2004 approach method. Research was conducted with Pen 60/70 asphalt content of 4%, 4.5%, 5%, 5.5%, and 6% to find the optimum asphalt content value, then it will be added with a ratio of 0%, 15%, 25%, and 35% marble fraction waste material to the total OAC weight. Results of the analysis of the Marshall characteristics of the porous asphalt mixture with a variation of 25% marble content have met the specifications on the grounds that all parameters have met the requirements of the Australian Asphalt Pavement Association (AAPA 2004) with a VIM value at 25% content of 18.61%, for a VMA value of 50.60%, while for a stability value of 508 kg and for a flow value obtained of 2.57 mm while for an MQ value of 262.46 kg/mm.